Two Faces of Fermented Foods—The Benefits and Threats of Its Consumption - Skowron, Krzysztof; Budzyńska, Anna; Grudlewska-Buda, Katarzyna; Wiktorczyk-Kapischke, Natalia; Andrzejewska, Małgorzata; Wałecka-Zacharska, Ewa; Gospodarek-Komkowska, Eugenia (Frontiers in Microbiology, 2022)
In underdeveloped and developing countries, due to poverty, fermentation is one of the most widely used preservation methods. It not only allows extending the shelf life of food, but also brings other benefits, including inhibiting the growth of pathogenic microorganisms, improving the organoleptic properties and product digestibility, and can be a valuable source of functional microorganisms. Today, there is a great interest in functional strains, which, in addition to typical probiotic strains, can participate in the treatment of numerous diseases, disorders of the digestive system, but also mental diseases, or stimulate our immune system. Hence, fermented foods and beverages are not only a part of the traditional diet, e.g., in Africa but also play a role in the nutrition of people around the world. The fermentation process for some products occurs spontaneously, without the use of well-defined starter cultures, under poorly controlled or uncontrolled conditions. Therefore, while this affordable technology has many advantages, it can also pose a potential health risk. The use of poor-quality ingredients, inadequate hygiene conditions in the manufacturing processes, the lack of standards for safety and hygiene controls lead to the failure food safety systems implementation, especially in low- and middle-income countries or for small-scale products (at household level, in villages and scale cottage industries). This can result in the presence of pathogenic microorganisms or their toxins in the food contributing to cases of illness or even outbreaks. Also, improper processing and storage, as by well as the conditions of sale affect the food safety. Foodborne diseases through the consumption of traditional fermented foods are not reported frequently, but this may be related, among other things, to a low percentage of people entering healthcare care or weaknesses in foodborne disease surveillance systems. In many parts of the world, especially in Africa and Asia, pathogens such as enterotoxigenic and enterohemorrhagic Escherichia coli, Shigella spp., Salmonella spp., enterotoxigenic Staphylococcus aureus, Listeria monocytogenes, and Bacillus cereus have been detected in fermented foods. Therefore, this review, in addition to the positive aspects, presents the potential risk associated with the consumption of this type of products.